(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
Knowledge of basic concepts in applied behavior analysis is critical to quality service delivery by behavior analysts. However, there is little research published in Brazil about courses that teach these concepts to direct care staff working with the elderly population. Considering the increase in diagnosis of major neurocognitive disorder (MND) and the fact that behavior problems are more common in this population, this paper describes a course that aimed to train professionals to identify and describe basic concepts relevant to managing problem behaviors in older adults with MND. Student performance was tested through pre- and post-tests in a multiple probe design. The results showed improvement in the participants’ performance after the course and maintenance of those results. Therefore, the course was effective in meeting its objective.